2000
DOI: 10.1002/1522-726x(200009)51:1<1::aid-ccd1>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and technical determinants of the complexity of percutaneous transluminal coronary angioplasty procedures: Analysis in relation to radiation exposure parameters

Abstract: Few data are available on the quantitative assessment of complexity (C), especially in relation to a patient's exposure to radiation. The relationship between several clinical (CFs), anatomic (AFs), and technical factors (TFs) versus fluoroscopy time (FT) was evaluated in 402 random percutaneous transluminal coronary angioplasty (PTCA) procedures. CFs were age, sex, single or multivessel disease, ejection fraction, and previous coronary artery bypass graft. AFs were assessed based on the American Heart Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 17 publications
4
30
0
2
Order By: Relevance
“…Indeed, previous works that aimed at defining a predictive score of the fluoroscopy duration revealed that other therapeutic characteristics had a significant impact: the number of complex lesions (according to American Heart Association/American College of Cardiology classification [27]), the bifurcation and ostial stenting, the severity of occlusions and the degree of the tortuosity of treated vessels [6,25]. Furthermore, our results cannot be easily extrapolated, since patients were not randomly sampled from different interventional cardiology units.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, previous works that aimed at defining a predictive score of the fluoroscopy duration revealed that other therapeutic characteristics had a significant impact: the number of complex lesions (according to American Heart Association/American College of Cardiology classification [27]), the bifurcation and ostial stenting, the severity of occlusions and the degree of the tortuosity of treated vessels [6,25]. Furthermore, our results cannot be easily extrapolated, since patients were not randomly sampled from different interventional cardiology units.…”
Section: Discussionmentioning
confidence: 83%
“…The procedure complexity and the practitioner's attitude towards radioprotection involve other mechanisms that affect the dose level ( Table 3). The impact of the practitioner may be attributable to a selection bias, but clinical and therapeutic variables (although insufficient to model the complexity of procedures as a whole [6,25]) allowed adjusting on such a potential bias. Moreover, the technical data collected in this sample allowed for studying precisely how the parameters of procedure optimisation impacted on the dose imparted to patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 In fact, technical and anatomic factors during procedures likely have the largest effect on an individual case x-ray exposure. 18,19 As the principal determinant of occupational radiation exposure for operators is patient scatter, reducing total energy to patients directly affects physician and staff exposures as well. 20 Clearly, efforts to reduce radiation exposure for both patient and staff need to be a critical part of every catheterization laboratory's quality improvement mission.…”
Section: Discussionmentioning
confidence: 99%
“…Because some variables such as body mass index, the treatment of complex lesions, and the different angulation of the X-ray tube may have biased the radiation dose, [11][12][13] we also tested our hypothesis in 6 cases of simultaneous left and right radial cannulation during fluoroscopy in the anteroposterior position of the X-ray tube. In these cases, a snapshot evaluation of the radiation dose to the operator's left arm Radiation dose at the wrist was significantly higher compared with the rest of the body, but this difference was significant only in the right radial approach group.…”
Section: Discussionmentioning
confidence: 99%